Theoretical Study of Parameters Affecting for a chaiotic system by Bifurcation Scenarios - Kh. Ajeel, Sadeq (University of Thi-Qar Journal of Science, 2019)
We modeled the appearance of scenario in quantum dot chaotic system with different of parameters. The system show chaotic manner .In addition, there is capability to introduce mixture of oscillation sad stability. The most calculation of the chaotic dynamics by the variation of the all parameters without external perturbation, as evidenced by bifurcation diagram. The diagram of capture rate explain increase the percentage of control to the system dynamics.